2013
DOI: 10.3400/avd.oa.13-00024
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Aneurysms in the Upper Limbs

Abstract: Objective: The purpose of this study was to review the experience of aneurysms in the upper limbs treated with surgery and assess the outcomes. Materials and Methods: This study retrospectively reviewed the medical records of five patients with upper extremity aneurysms treated with surgical resection at Tokyo Medical and Dental University Hospital between March 2000 and February 2012. These patients were treated with excision surgery either with or without reconstructive surgery. Results: Two of the five pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…Igari et al previously reported five aneurysms of the upper limbs from 2000 to 2012, and only one of the aneurysms was a true BA aneurysm with an asymptomatic mass. 6 The Cleveland and the Mayo Clinics identified only one case of a true BA aneurysm in 581 brachial artery reconstructions performed between January 1989 and December 2000, 7 and only two cases over a 20-year period, 1 respectively. Although we have often treated false aneurysms or shunt blood vessel dilatation or aneurysms in the upper limbs, the present true BA aneurysm is the first case in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Igari et al previously reported five aneurysms of the upper limbs from 2000 to 2012, and only one of the aneurysms was a true BA aneurysm with an asymptomatic mass. 6 The Cleveland and the Mayo Clinics identified only one case of a true BA aneurysm in 581 brachial artery reconstructions performed between January 1989 and December 2000, 7 and only two cases over a 20-year period, 1 respectively. Although we have often treated false aneurysms or shunt blood vessel dilatation or aneurysms in the upper limbs, the present true BA aneurysm is the first case in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of resection of the lesion allowing decompression if necessary [ 18 ]. This treatment may be associated or not with revascularization depending on the presence of adequate perfusion of the limb and hand [ 19 ]. Suture removal and venous bypass to restore vascular anatomy are the techniques used to carry out revascularization [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors propose endovascular procedures such as angioplasty with stent or stent grafting, or embolization by interventional radiography [ 5 , 17 ]. These alternative options remain controversial [ 19 ]. In 2004, Komorowska-Timek et al reported the successful use of ultrasound-guided thrombin injection in the treatment of a false radial artery aneurysm at 3 cm and another false ulnar artery aneurysm at 2.5 cm resulting from arterial trauma during a failed catheterization [ 3 , 5 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoaneurysmen der A. ulnaris sind extrem seltene Ereignisse, über die es nur vereinzelt Fallberichte gibt [1]. Die Entstehung eines Pseudoaneurysmas der A. ulnaris wird mit penetrierenden Traumen, Kanülierungen der A. ulnaris, mit dem Hypothenar-Hammer-Syndrom oder perioperativen Traumen assoziiert [2].…”
Section: Diskussionunclassified